Theatre Lighting Before Electricity (Wesleyan University Press, 1978)
Theatre Lighting Before Electricity covers the intricacies of dealing with stage lighting before the advent of electricity. Ranging from ancient Greek times to 1882, theater historian Frederick Penzel (shows that theatre lighting has a long and ingenious history. As early as the sixteenth century, Italian theatres had colored lighting displays. Scenes were lighted by large central chandeliers, and early forms of sidelights, reflectors, and floodlights were in use. Lighting was adjusted to create moods or to reinforce dramatic actions. Gaslighting was first generally used in theatres in 1817 and before the end of that year the most important London theatres were completely illuminated by gaslight. Penzel demonstrates that by the time electricity had come into use, most modem stage lighting devices had been in development for many years, and were only being modified for use with a more powerful light source. Originally published in 1978, this was the first written history of early theatre lighting and contains many valuable technical illustrations. This book continues to present an unparalleled resource on early stage lighting.